Educational Model for Character Development on the Basis of Role Sustainable Models - Abd. Syakur; Bambang Sumardjoko; Harsono Harsono (Universitas Pahlawan Tuanku Tambusai, 2022)
Education is a crucial factor in determining whether or not character education is implemented. Character education is extremely important because, with character, humans will become noble and special beings when compared to other creatures, and even when compared to their fellow humans. Because of the critical importance of character education, the existence of character education methods and approaches is one of the role models to achieving an essential character both in attitude and action. Character education methods and approaches include: The purpose of this research is to develop an exemplary method for character development. By employing the Systematic Literature Review (SLR) method of research, we have discovered that exemplary character education is an effective method and approach when implemented comprehensively by educators in every educational environment, with a particular emphasis on cognitive, affective, and psychomotor aspects. These three aspects are the driving force for all groups, both in terms of behavior and daily activitie